The use of dexmedetomidine in agitation in children: a literature review (Research, Society and Development, 2022)
Introduction: The incidence of postoperative agitation in children under general anesthesia is high, and can be manifested by several behaviors, such as crying, irritability, intense agitation and disorientation, which in many cases require mechanical restraint. The use of dexmedetomidine in this situation is well described by several authors. This sedative provides a “conscious sedation” to the patient, where they appear to be asleep but can be easily aroused without respiratory depression. Objectives: To review the literature on the use of dexmedetomidine to control agitation in children undergoing operative anesthesia, in addition to comparing the use of other sedatives, such as ketamine, with dexmedetomidine. Methodology: Narrative bibliographic review, through data collection, using the Scielo, MedLine and PubMed database platforms, with the descriptors: “dexmedetomidine” AND “psychomotor agitation” AND “child” OR “clonidine” AND "ketamine". Results and Conclusion: Most studies have shown that dexmedetomidine is well applied to agitation in children, promoting postoperative pain relief, with a low incidence of adverse events, and thus can be used safely. In addition, other drugs, such as ketamine, have also shown satisfactory results for the prevention of postoperative agitation in children.